Effect of organic fertilizer types and dosage on yield and nutrient uptake of red ginger in an Alfisol - SETYANINGRUM, DESY; SUHITA, CAHYANINGTYAS PUTRI; PARYANTO, EDI; NINGSIH, HARDIAN; ARIFIN, ZAINAL; SURYADI, DIDIK; SUPRIHATIN, DEWI NAWANG; NURHIDAYATI, FEBRY; PRADANA, ANDITYA GILANG RIZKY; HANTARI, DIMAR (Asian Journal of Agriculture, 2025)
Abstract. Setyaningrum D, Suhita CP, Paryanto E, Ningsih H, Arifin Z, Suryadi D, Suprihatin DN, Nurhidayati F, Pradana AGR, Hantari D. 2025. Effect of organic fertilizer types and dosage on yield and nutrient uptake of red ginger in an Alfisol. Asian J Agric 9: 636-644. Declining red ginger production in Indonesia, partly due to reduced optimal land availability, has prompted the use of suboptimal soils, such as Alfisols are known to be fertile soils with relatively high concentrations of essential nutrients. This study evaluated the effects of animal manure type (cow, goat, and chicken) and application dosage (0, 10, 20, and 30 tons.ha-¹) on yield performance and nitrogen (N), phosphorus (P), and potassium (K) uptake of red ginger (Zingiber officinale var. rubrum) in Alfisol. A randomized complete block design with a split-plot arrangement was applied. Results showed that both manure type and dosage significantly influenced yield and nutrient uptake. Goat manure at 30 tons.ha?¹ produced the highest fresh weight, biomass, rhizome weight, and N and P uptake. Rhizome weight and volume were positively correlated with N and P uptake, indicating that improved nutrient absorption efficiency contributed to yield enhancement. Increasing manure dosage consistently elevated biomass, rhizome volume, and K uptake, with optimal results at 30 tons.ha-¹. These findings demonstrate that organic fertilization, particularly with goat manure at 30 tons.ha-¹, is an effective strategy to boost red ginger productivity and nutrient use efficiency on marginal Alfisol soil. The approach supports sustainable cultivation and could help meet increasing market demand, although long-term impacts on soil health require further investigation.